2019
DOI: 10.3390/nu11122925
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Fruit and Vegetable Gardens in Early Years Settings in England: Results from a Cross-Sectional Survey of Nurseries

Abstract: Garden-based interventions may increase child intake of fruits and vegetables and offset food costs, but few have been conducted in early care and education (ECE). This study assessed whether nurseries were interested in and perceived any barriers to growing fruits and vegetables. Surveys were mailed to a cross-sectional sample of nurseries in 2012–2013 throughout England. Nurseries were stratified based on socioeconomic status as most, middle, or least deprived areas. We fit logistic regression models to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Third, the low overall response rate (7.8%) may limit generalizability of survey results. Prior studies similar in nature have garnered response rates around 50% [ 11 , 42 , 43 ]. The low response rate in this survey is likely due to the impacts of the COVID-19 pandemic itself.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the low overall response rate (7.8%) may limit generalizability of survey results. Prior studies similar in nature have garnered response rates around 50% [ 11 , 42 , 43 ]. The low response rate in this survey is likely due to the impacts of the COVID-19 pandemic itself.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, around half of the services in our study used some food from their edible gardens in their menus. Edible gardens are a popular choice in childcare services, with a New Zealand study reporting that nearly all (89·5 %) of their 257 services had an edible garden onsite ( 41 ) , and a UK study indicating that most childcare services (81 %) were interested in growing their own garden; however, the UK study indicated that space, time and expertise were barriers ( 42 ) . Additionally, it may take more time to plan a menu responsive to seasonal food availability, procure sustainably and prepare more plant- and whole grain-based meals, further contributing to resourcing and cost challenges of sustainable meals ( 43 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the study of Lehto et al [19] did not find any influence of center cooking facilities, resources, or staff education on children's intake, which might imply that a lack of resources and facilities does not necessarily hinder healthy dietary intake. Benjamin Neelon and colleagues [21] also examined barriers to the implementation of intervention in childcare settings, though specifically for fruit and vegetable gardens. Fruit and vegetable garden projects have been previously shown to increase children's intake of fruit and vegetables (e.g., [22], but to date few interventions in Early Care and Education settings have included gardening [23]).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit and vegetable garden projects have been previously shown to increase children's intake of fruit and vegetables (e.g., [22], but to date few interventions in Early Care and Education settings have included gardening [23]). Benjamin Neelon and colleagues [21] showed that although the majority (81%) of the English childcare settings was interested in implementing gardens, various practical barriers hindered actual implementation, including lack of space, expertise and time. This is in line with the findings of Holley and colleagues [24], who identified various barriers and challenges for free food provision at holiday clubs to tackle children's hunger.…”
Section: Introductionmentioning
confidence: 99%